Sectoral impact of bank credit in Malaysia: ARDL modelling approach - Abubakar, Abdulsalam; Kassim, Salina (Universiti Putra Malaysia Press, 2016)
This study investigates the sectoral impacts of bank credit on economic output by analysing the long- and short-run effects of bank credit on the output of five major economic sectors in Malaysia. The sectors are the agriculture, manufacturing, mining and quarrying, construction and services sectors. It employed quarterly data from 1997Q1 to 2014Q4 and adopted the ARDL and ECM approaches. The results revealed that bank credit has uneven impacts on the economic sectors, with significant effects, particularly in the short run on the mining and quarrying, and manufacturing sectors, but no effect on the agriculture sector. In contrast, bank credit is found to have larger long-run impact on output of the construction and services sectors compared to the short run. Hence, the results suggest the importance of considering the sectoral-specific characteristics in extending bank financing to ensure the effectiveness of financing in supporting the growth of the sector. As for the agriculture sector, concessionary financing is needed since it is shown that the sector is not adequately being served by the banking system.